Synthesis and characterization of flexible polydimethylsiloxane containing resin for 3D SLA printers - ÇAKIR, MUSTAFA; AKIN, EMRE (My University, 2021)
As well known, epoxy acrylate resins has been widely used in 3D SLA printers applications. Epoxy acrylate system that consisted of bisphenol-A glycerolate diacrylate (epoxy acrylate resin) and 1,6-Hexanediol diacrylate ( HDDA, reactive diluent resin) were used in this study. The weight ratio of Bisphenol-A glycerolate diacrylate and HDDA was determined as 1/1. The purpose of this study is to develop a novel epoxy acrylate system for 3D SLA printers and observe its properties. For this reason, a novel polydimethylsiloxane containing urethane acrylate was synthesized as reactive resin and added into epoxy acrylate system with various weight percents. It is also well known that polydimethylsiloxanes increase thermal properties of polymer materials. In order to obtain this novel reactice urethane acrylate resin, hydroxyl terminated polydimethylsiloxane was used as backbone of the chain while isophorone diisocyanate (IPDI) and 2-Hydroxyethyl methacrylate (HEMA) were used for synthesizing urethane acrylate functional groups. The addition of this novel reactive resin was carried out up to 1.5 % into epoxy acrylate system. Mechanical and physical tests were applied to the produced samples such as tensile, Shore-D hardness, abrasive and density tests. Considering of the results, tensile strength and modulus exhibited substantial increases while tensile strain presented large decreases. Taber abrasive resistance showed considerable increases. While Shore-D hardness of the produced novel materials presented slight decreases, the densities showed almost no change
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)